2017
DOI: 10.1016/j.ajo.2017.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Efficacy, Predictability, Safety, and Visual Quality of Laser Corneal Refractive Surgery: A Network Meta-analysis

Abstract: This network meta-analysis shows that there were no statistically significant differences in either visual outcomes (efficacy and safety) or visual quality (HOAs and CS). FS-LASIK behaved better in predictability than any other type of surgeries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 56 publications
2
89
0
3
Order By: Relevance
“…50 Most recently, a network-based meta-analysis comparing the postoperative efficacy, predictability, safety and visual quality of all major forms of laser corneal refractive surgeries (PRK, LASEK, Epi-LASIK, trasepithelial PRK, LASIK, femtosecond assisted [FS-LASIK], small incision lenticule extraction and femtosecond lenticule extraction) for correcting myopia was published. 51 Based on analysis of 48 RCTs, the authors concluded that this network meta-analysis showed that there were no statistically significant differences in both visual outcomes (efficacy and safety) and visual quality (higher-order aberrations and contrast sensitivity) between the techniques. FS-LASIK behaved better in predictability than any other type of surgery.…”
Section: Laser Ablation Algorithmsmentioning
confidence: 98%
“…50 Most recently, a network-based meta-analysis comparing the postoperative efficacy, predictability, safety and visual quality of all major forms of laser corneal refractive surgeries (PRK, LASEK, Epi-LASIK, trasepithelial PRK, LASIK, femtosecond assisted [FS-LASIK], small incision lenticule extraction and femtosecond lenticule extraction) for correcting myopia was published. 51 Based on analysis of 48 RCTs, the authors concluded that this network meta-analysis showed that there were no statistically significant differences in both visual outcomes (efficacy and safety) and visual quality (higher-order aberrations and contrast sensitivity) between the techniques. FS-LASIK behaved better in predictability than any other type of surgery.…”
Section: Laser Ablation Algorithmsmentioning
confidence: 98%
“…The paradigm of Lasek surgery is to restore the epithelium immediately after stromal photoablation with the aid of dilute alcohol [15]. There is a debate about the interest of replacing the epithelial flap in terms of decreased speed recovery and pain [16,17]. Theoretically, on the one hand, it has flap creation advantages with less discomfort and possibly increased recovery speed; on the other hand, the safety of PRK.…”
Section: Lasek and Its Advantagesmentioning
confidence: 99%
“…Ang RE et al [10] and Zhang Y et al [11] were reported that flap-off epi-LASIK with MMC has less pain, corneal haze and faster visual recovery, while visual results, refractive outcomes, contrast sensitivity (CS), and higher-order aberrations (HOAs) were comparable with flap-on epi-LASIK. Wen D and associates [12] published a network meta-analysis to comparative evaluation the visual outcomes and visual quality, the report shows that there were no statistically significant difference in either visual outcomes (efficacy and safety) or visual quality (HOAs and CS), but femto-LASIK behaved better in predictability than any other type of surgeries. Additionally, the thinner corneas, higher intraocular pressure (IOP), and higher myopia requiring greater laser ablation are more predisposed to the anterior shift of the cornea.…”
Section: Introductionmentioning
confidence: 99%